Взаимосвязь шероховатости обработанной поверхности, радиальной составляющей силы резания и производительности при точении резцами из киборита закаленной стали ШХ15 - Мановицкий, А.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Interaction of surface profiles analysis when turning of hardened steels with cutting tools
equipped by polycrystalline cubic Boron Nitride with radial cutting force and productivity of turning
is presented. After the measuring of machined part surface roughness with profile analyzer as
well as radial force components obtained with dynamometric instrument the data are maintained to
determine the ratio of profile heights to radial force divided by productivity of process.